2021
DOI: 10.29133/yyutbd.768736
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Stress on Some Growth and Physiological Parameters of Peanut (Arachis hypogea L.) Varieties

Abstract: Bu çalışmada, yerfıstığı (Arachis hypogea L.) çeşitlerinin (Arıoğlu-2003 ve Gazipaşa) bazı büyüme ve fizyolojik parametreleri üzerine tuz stresinin (0, 100, 200 mM NaCl) etkisi araştırılmıştır. Deneme, Tesadüf Parselleri Deneme Deseni' ne göre faktöriyel düzende 3 tekerrürlü olarak tam kontrollü iklim odasında yürütülmüştür. Araştırma sonucunda; tuz stresinin gövde uzunluğu, kök yaş ve kuru ağırlığı üzerine etkisi istatistiksel olarak önemsiz bulunmuştur. Artan tuz konsantrasyonları yaprak dokularında iyon sız… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…In a conducted experiment on the effect of salt stress on soybean plant by Kumari et al, (2015), they found that MDA values increases with the increase of salt stress. The same result was discovered on other crops (Sairam and Srivastava, 2002;Porcel et al,2003;Yildirim et al, 2004;Han and Lee, 2005;Shukla et al, 2012;Yolci et al 2021). HA had a significant effect on the soybean plants for MDA.…”
Section: Findings and Discussionsupporting
confidence: 74%
“…In a conducted experiment on the effect of salt stress on soybean plant by Kumari et al, (2015), they found that MDA values increases with the increase of salt stress. The same result was discovered on other crops (Sairam and Srivastava, 2002;Porcel et al,2003;Yildirim et al, 2004;Han and Lee, 2005;Shukla et al, 2012;Yolci et al 2021). HA had a significant effect on the soybean plants for MDA.…”
Section: Findings and Discussionsupporting
confidence: 74%